2020
DOI: 10.1111/vde.12859
|View full text |Cite
|
Sign up to set email alerts
|

A moisturizer formulated with glycerol and propylene glycol accelerates the recovery of skin barrier function after experimental disruption in dogs

Abstract: Background Moisturizers are foundational therapies for human atopic dermatitis. In veterinary medicine, the use of moisturizers has been recommended by an expert committee to alleviate skin dryness that would occur, for example, in canine atopic dermatitis (cAD). However, little is known regarding the effects of moisturizers on the skin barrier. Hypothesis/Objectives To investigate the effects of a moisturizer on skin barrier recovery in a canine model of chronic mechanical barrier disruption. Animals Six heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Considering that hydrating the skin method alleviates AD symptoms in dogs, and the fact that dry skin is the main symptom of CAD ( 40 , 41 ), RH is expected to affect CAD in humans. Additionally, the inverse correlation between endotoxin and AD was previously reported in humans and dogs ( 11 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that hydrating the skin method alleviates AD symptoms in dogs, and the fact that dry skin is the main symptom of CAD ( 40 , 41 ), RH is expected to affect CAD in humans. Additionally, the inverse correlation between endotoxin and AD was previously reported in humans and dogs ( 11 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The topical application of lipid-based formulations aimed at improving skin barrier dysfunction has been previously investigated in several studies in dogs [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These interventions have shown some positive effects on skin health, and they are normally delivered in the form of a spot-on or a shampoo presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The topical application of lipid-based formulations aimed at improving skin barrier dysfunction has been previously investigated in several studies in dogs [32][33][34][35][36][37][38][39][40][41][42][43]. These…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, in cAD, TP corresponds to the treatment of flares, or "reactive therapy"; SP corresponds to the prevention of flares, or "proactive therapy"; and PP corresponds to strategies or interventions that are implemented to avoid the development of the disease altogether. However, while there is extensive research to develop and improve existing treatments [7,27,28,30,33,35,[39][40][41][42][43] and even to develop proactive strategies [21,44], cAD primary prevention is entirely neglected. Despite Marsella (2013) suggesting that skin barrier repair interventions could prove beneficial when initiated in early life in cAD's predisposed breeds [45], research on these strategies has not been pursued.…”
Section: What Is Prevention?mentioning
confidence: 99%
“…Furthermore, a previous study showed that an essential fatty acid supplementation had a steroid-sparing effect in atopic dogs, which could be explained by a possible skin barrier improvement [110]. Although extensive research exists on strategies directed at the external skin surface to improve skin barrier function in cAD management [1,14,28,39,67,[111][112][113][114][115][116][117][118][119][120][121][122][123][124], there are, as yet, no studies on cAD prevention to the authors' knowledge.…”
Section: Primary Prevention Strategies In Dogsmentioning
confidence: 99%